Reflective analysis of the article "The Rwandan Genocide: Analysis of the factors that influenced the conflict - Reinel Yorwaldy Pino Peñaranda (Postulados: Revista Sociojurídica)
This essay is written as a research project within the Master’s program in International Humanitarian Law, Human Rights, and Operational Law at the University of Nebrija in Spain. The primary objective of this work is to conduct a reflective and critical analysis of Rodríguez Vázquez’s (2017) article titled “The Genocide in Rwanda: Analysis of the Factors Influencing the Conflict.” Various crucial aspects will be explored, such as the influence of European colonization in fostering a growing message of discrimination, the role played by global powers in the conflict, the economic interests that still surround Rwanda today, and the significant influence of religion as a key factor in the genocide.The analysis will focus on unraveling the complexities of these factors, reflecting on the author’s conclusions, as articulated in their study. However, we will enhance this essay by proposing new key points that will contribute to a deeper reflection on the impact of the Rwandan genocide on the international stage and the understanding of its historical and contemporary roots.